Effect of organised cervical cancer screening on cervical cancer mortality in Europe: a systematic review. (March 2020) - Jansen, Erik E.L.; Zielonke, Nadine; Gini, Andrea; Anttila, Ahti; Segnan, Nereo; Vokó, Zoltán; Ivanuš, Urška; McKee, Martin; de Koning, Harry J.; de Kok, Inge M.C.M.; ,; Veerus, Piret; et al.
Abstract: Background: Organised cervical cancer (CC) screening programmes are delivered in many different ways across the European Union and its regions. Our aim was to systematically review the impact of these programs on CC mortality. Methods: Two independent reviewers identified all eligible studies investigating the effect of organised screening on CC mortality in Europe. Six databases including Embase, Medline and Web of Science were searched (March 2018) with predefined inclusion and exclusion criteria. Only original studies with at least five years of follow-up were considered. Validated tools were used to assess the risk of bias of the included studies. Results: Ten observational studies were included: seven cohort and three case-control studies. No randomised controlled trials were found, and there were no eligible studies from the eastern and southern part of Europe. Among the eligible studies, seven were conducted in the twentieth century; they scored lower on the risk of bias assessment. CC mortality reduction for women attending organised screening vs. non-attenders ranged from 41% to 92% in seven studies. Reductions were similar in Western (45–92%) and Northern (41–87%) Europe and were higher in the three more recent studies (66–92%). For invited vs. non-invited women, this reduction ranged from 17% to 79% in five studies. Conclusion: Although data were lacking in Southern and Eastern Europe and the effect size varied between countries and studies, this systematic review provides evidence that organised CC screening reduces CC mortality in those parts of Europe where CC screening was implemented and monitored. Highlights: No randomised controlled trials have been performed assessing mortality reduction after cervical cancer screening. Observational studies show a 41%–92% mortality reduction after attending cervical screening. Inviting women for screening was found to result in a 17%–79% mortality reduction. Similar results from Northern and Western Europe and no studies from Southern and Eastern Europe.